The Role of Virtual Reality in Personalized Medicine: Advancing Prediction, Prevention, and Participation. - Miltiadis, Ilias; Skarlis, Apostolos; Burko, Pavel (Journal of Medical Systems, 2025)
The integration of virtual reality (VR) technology into medicine represents a transformative step toward the realization of 4P medicine, characterized by personalization, prediction, prevention, and participation. VR provides an immersive platform for addressing neurological and mental disorders by tailoring virtual environments to individual patient needs, enhancing diagnostic precision, and improving therapeutic outcomes. This paper explores the applications of VR within the framework of 4P medicine, emphasizing its potential in neurorehabilitation, stress reduction, and patient engagement. The personalization aspect of VR enables the design of customized scenarios for therapeutic interventions. Predictive capabilities allow for early detection and mitigation of complications through simulated environments that analyze patient responses. In preventive medicine, VR fosters stress and anxiety reduction, which directly influences patient well-being and quality of life. Participation is enhanced by VR's interactive nature, transforming patients from passive recipients of care to active participants in their treatment journey. Despite its promise, VR faces limitations, including simulator sickness, technical challenges, and accessibility barriers. These factors highlight the need for methodological standardization, improved hardware, and enhanced training for medical professionals. Additionally, a lack of longitudinal studies and safety monitoring systems restricts the widespread clinical adoption of VR. As healthcare systems continue to adapt to technological advancements, VR has the potential to emerge as a pivotal tool in personalized medicine, offering innovative solutions for complex neurological and mental health challenges. By addressing current limitations, VR may redefine patient care and mark a significant milestone in the evolution of evidence-based medical practice.